2023
DOI: 10.1039/d3sc00020f
|View full text |Cite
|
Sign up to set email alerts
|

An orthogonally activatable CRISPR-Cas13d nanoprodrug to reverse chemoresistance for enhanced chemo-photodynamic therapy

Abstract: Orthogonal therapy that combines CRISPR-based gene editing and prodrug-based chemotherapy is a promising approach to combat multidrug-resistant cancer. However, its potency to precisely regulate different therapeutic modalities in vivo is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…From this perspective, Z. Liu et al have developed a UCNP-based drug-delivery system for synergistic anticancer therapy [218] (Figure 14). To develop an advanced therapeutic system, they synthesized a green light-activatable anticancer prodrug and UV light activatable gene-gene editing sequences.…”
Section: Photo-responsive Nanoparticle Drug-delivery Systems For Anti...mentioning
confidence: 99%
“…From this perspective, Z. Liu et al have developed a UCNP-based drug-delivery system for synergistic anticancer therapy [218] (Figure 14). To develop an advanced therapeutic system, they synthesized a green light-activatable anticancer prodrug and UV light activatable gene-gene editing sequences.…”
Section: Photo-responsive Nanoparticle Drug-delivery Systems For Anti...mentioning
confidence: 99%
“…Liu et al graded controlled functional blocks for synergistic therapy using orthogonal emissions from UCNPs (Figure 8c). [229] Ho 3+ emission under 980 nm excitation activated Pt (IV) prodrugs. The emitted photons were absorbed by an RB photosensitizer for PDT.…”
Section: All-in-one Therapymentioning
confidence: 99%
“…c) The construction of nanodrugs for combined cancer phototherapy and description of the functions of every component. Reproduced with permission [229]. Copyright 2023, Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…Specifically, the cationic polymer was synthesized by simple covalent modification of PLL with the Rose Bengal (RB) photosensitizer, whose absorbance spectra exhibit a maximum overlap with the green upconversion luminescence band of UCNPs. 39 Considering that commercial dBET6 is a heterobifunctional small molecule for BRD4 protein degradation, 40 we use dBET6 as a model PROTAC to disrupt the oncogenic processes. We demonstrated that USDPR exhibits outstanding competencies of membrane disruption by the ROS generated via the energy transferred from the UCNPs to photosensitizers for efficiently boosting the endo/lysosomal escape of PROTACs into the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%